The Issues of Hospitality and Tourism Education in Malaysia - Mohd Fadil Mohd Yusof (2010)
Malaysian hospitality and tourism industry has experienced a remarkable growth and received strong support from the government. The industry is recognized as one of the major industries in providing foreign exchange earnings and generating employment to the people. Therefore, the need for training in tourism and hospitality in upgrading the competencies level of workforce to participate in the industry is very important. Over the last 30 years, the number of tourism and hospitality education program in Malaysia has increased significantly. Presently, tourism and hospitality education is offered by a number of public and private universities, colleges and polytechnics. This paper describes some of the research issues and concerns pertaining to the hospitality and tourism education in Malaysia. The objectives of this study are to critically examine the content of the tourism and hospitality curriculum offered by relevant higher learning institutions and to determine whether the present curriculum contents are what have been expected by the relevant stakeholders such as educators and industry practitioners. This proposed study will be beneficial to the academics in the relevant field in designing an effective hospitality curriculum which is flexible and well adapted to the dynamic environment. The expected outcome of the study provides educators a guideline as what the contents of the program should be focused on in order to prepare competent graduates to enter the hospitality job market.